Serous macular detachment, yellow macular deposits, and prominent middle limiting membrane in multiple myeloma - Dogan B; Erol MK; Toslak D; Coban DT; Bulut M; Cengiz A; Sarı ES (Dove Medical Press, 2015)
Berna Dogan,1 Muhammet Kazim Erol,1 Devrim Toslak,1 Deniz Turgut Coban,1 Mehmet Bulut,1 Ayse Cengiz,1 Esin Sogutlu Sari2 1Antalya Training and Research Hospital, Eye Clinic, Antalya, Turkey; 2Balikesir University Medicine Faculty, Eye Clinic, Balikesir, Turkey Abstract: Bone marrow-derived multiple myeloma is a type of plasma cell tumor that may be associated with ocular complications. A 52-year-old male patient was admitted to our eye clinic with the complaint of sudden visual loss and a visual acuity of 20/50 in the right eye and 20/800 in the left eye. Fundus examination revealed common flame-shaped hemorrhages, venous dilatation and tortuosity, Roth spots, serous macular detachment, and yellow macular deposits in both eyes. Evaluation with fundus fluorescein angiography, fundus autofluorescence, and spectral-domain optical coherence tomography resulted in suspicion of hyperviscosity retinopathy and referral to the hematology clinic. After hematology consultation confirmed a diagnosis of multiple myeloma, chemotherapy and plasmapheresis were initiated. Four months after presentation, best-corrected visual acuity was 20/20 in both eyes and improvement in hyperviscosity retinopathy, serous macular detachment, and yellow macular deposits was observed. Keywords: serous macular detachment, yellow macular deposit, prominent middle limiting membrane, multiple myeloma